The precocity-longevity hypothesis re-examined: Does career start age in Canadian National Hockey League players influence length of lifespan? - Lemez, S.; Wattie, N.; Ardern, C. I.; Baker, J. (Journal of Sports Science & Medicine, 2014)
This study explored the precocity-longevity hypothesis among Canadian-born National Hockey League (NHL) players. Based on the link between high career achievement and early mortality identified in previous research, we hypothesized that precocious NHL players would have shorter lifespans than those debuting at later ages. There have been 4,583 Canadian-born NHL players who debuted between 1917 and 2010 (Quant Hockey, 2014); however, we only analyzed those who debuted between 1917 and 1986 (n = 2, 971) to limit the influence of players who were still living (i.e., censored cases). Additionally, we restricted our sample to Canadian players to limit the influence of different developmental systems and socio-cultural factors that might affect longevity. Data were collected through the official website of the hockey hall of fame (www.hhof.com), and a random sample (~10%) was cross-referenced within Total Hockey (Diamond et al., 1998) and www.hockey-reference.com which confirmed complete agreement.